PEMANFAATAN LAHAN DIANTARA TANAMAN JAMBU METE MUDA DI LAHAN MARGINAL - Pranowo, Dibyo; Purwanto, Eko Heri (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The use of space among young cashew trees in marginal lands. Cashew trees are mostly planted in monoculture way, so it would be not efficient in using the space of lands. As the crops widely planted and increase of their canopy with its ages, there is avail able space that might be used for growing crops, particulary those do not need full intensity of the sun. This enable many annual crops such as corn, peanuts, upland rice that may be grown among the trees. The use of annual crops should take into account their tolency to the sun intensity. The cashew trees having root system which develop laterally need certain technology that might be develepod. Some intercrops that might be suitable be grown among them are corn, peanut, and upland rice. Previous results revealed that growing annual crops like corn yielded of 4.5 ton/ha, peanut of 975 k g/ha, and combination of the both of 3981 kg/ha and 308 kg/ha, while those of situbagendit upland rice yielded of 2.9 ton. The results showed that growing the intercrops among the cashew tress may give reasonable income for farmers as alternatively solution in optimizing of the space of lands between cashew rees.